At a meeting in the town of Erdek from left to right: B. Meral, chairman of Yol-is, and the chairman of Türk-iş: S. Yilmaz
At a meeting in the town of Erdek from left to right: B. Meral, chairman of Yol-is, and the chairman of Türk-iş: S. Yilmaz.